Terraform Sustainability Assessment Framework for Bioregenerative Life Support Systems - Irons, Morgan A.; Irons, Lee G. (Frontiers in Astronomy and Space Sciences, 2021)
In this perspective paper, we raise attention to the lack of methods or data to measure claims of sustainability for bioregenerative life support system designs, even though sustainability is used as a critical mission criterion for deep space exploration. The result is a lack of coherence in the literature in the use of the word sustainability and the application of the criterion. We review a generalized resilient design framework for quantifying the engineered resilience of any environmental control and life support system, and explain how it carries assumptions that do not fit the assumptions of sustainability that come out of environmental science. Any quantitative method of assessing sustainability must apply the correct assumptions. We explain the basis of bioregenerative life support system sustainability in the context of seven theoretical frameworks: a planet with biogeochemical cycles; human consumption as loads and disturbances; human supply chains; forced and natural cycles; fragmented ecosystems; ecosystems as a network of consumer-resource interactions with critical factors occurring at ecosystem control points; and stability of human consumer resources. We then explain the properties of environmental stability, examine a method of quantifying resistance and resilience that are impacted by disturbances, extend this method to quantifying consistence and persistence that are impacted by feedback from loads, and propose use of these equations in a sustainability assessment framework for the bioregenerative life support system. We then propose a framework for normalizing the quantified sustainability properties of a bioregenerative life support system using the Earth model to control for variance.